2011
DOI: 10.1002/pds.2184
|View full text |Cite
|
Sign up to set email alerts
|

Prescription drug use during pregnancy in developed countries: a systematic review

Abstract: Purpose-To review the literature describing patterns of out-patient prescription drug use during pregnancy by therapeutic category, potential for fetal harm, and overall.Methods-We conducted a systematic review of peer-reviewed literature published from 1989 to 2010. We included studies evaluating individual-level exposures to prescription medicines during pregnancy. We selected only studies conducted in developed (OECD) countries and published in English.Results-Published drug utilization studies reveal wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
164
3
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(194 citation statements)
references
References 24 publications
12
164
3
15
Order By: Relevance
“…Quanto às categorias de risco do uso de medicamentos segundo o FDA, o maior consumo foi das classes A, B e C. Elas são representadas por medicamentos para distúrbios do funcionamento gastrointestinal e preparações antianêmicas 17 . A classe A é a mais utilizada na gravidez, conforme evidenciado em uma revisão sistemática realizada por Daw et al 31 que apresentou maior consumo dessa classe em alguns países como França e Alemanha.…”
Section: Discussionunclassified
“…Quanto às categorias de risco do uso de medicamentos segundo o FDA, o maior consumo foi das classes A, B e C. Elas são representadas por medicamentos para distúrbios do funcionamento gastrointestinal e preparações antianêmicas 17 . A classe A é a mais utilizada na gravidez, conforme evidenciado em uma revisão sistemática realizada por Daw et al 31 que apresentou maior consumo dessa classe em alguns países como França e Alemanha.…”
Section: Discussionunclassified
“…According to literature, a recent systematic review of drug utilization studies showed a wide variation of drug use during pregnancy in developed countries, which was from 27 to 93% (Daw et al, 2011). The prevalence of medication use among pregnant women in Brazil varied from 80 to 94.6% (Brum et al, 2011;Fonseca et al, 2002;Geib et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…(Daw et al, 2011;Mitchell et al, 2011). Before the disaster caused by the use of thalidomide in the late 1950s and early 1960s, placenta was considered a barrier capable of protecting the fetus from any pharmacological damage (Lenz, 1962;Martinez-Frias et al, 2012;Oliveira et al, 1999;Papaseita et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Almost all categories of drugs are prescribed during pregnancy depending on the illness. [8][9][10][11] Mashayekhi et al have evaluated the awareness among pregnant women with regard to effect of drugs on fetus. 12 Drug use behavior in pregnant women in rural India has been investigated.…”
Section: Introductionmentioning
confidence: 99%